A cross-cultural study of visual attention in autism spectrum disorder. Issue 3 (3rd April 2023) - Nayar, Kritika; Kang, Xin; Winston, Molly; Wong, Patrick; Losh, Molly
ABSTRACT: Differences in visual attention have been documented in ASD, and appear linked to clinical symptoms. However, most research has been conducted in Western cultures. Because striking differences in visual attention patterns have been documented in other cultures, it is important to understand how culture may influence attentional patterns in ASD. This study compared differences in visual attention in ASD across Western and East Asian cultures, where differences in attention to contextual and global information have been repeatedly demonstrated, to investigate potential culturally-specific ASD phenotypes. One hundred thirty-two total participants included individuals with ASD ( n  = 24) and controls ( n  = 47) from Hong Kong (HK), along with a previously studied group of age- and IQ-comparable participants from the United States ( n  = 26 ASD; n  = 35 control). Gaze was tracked while participants completed two narrative tasks that differed in social-emotional complexity. Proportions of fixations to face, bodies, and setting were examined across groups using linear mixed-effect models and a series of growth curve models. Cultural differences were found across tasks and groups. Both the ASD and control HK groups attended more to global contextual setting information, more to the body regions, and less toward faces of characters compared to US groups. Growth curve models indicated that these differences attenuated over time in certain stimuli. ASD-related effects were only observed in the more complex stimuli depicting characters with ambiguous facial expressions. Findings indicate a notable cultural influence on visual attention patterns in ASD, and underscore the importance of stimuli complexity in differentiating cultural versus diagnostic effects on attentional styles.